1990
DOI: 10.1097/00006123-199001000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Boron neutron capture therapy of a rat glioma

Abstract: The purpose of the present study was to utilize a well-established rat glioma to evaluate boron neutron capture therapy for the treatment of malignant brain tumors. Boron-10 (10B) is a stable isotope which, when irradiated with thermal neutrons, produces a capture reaction yielding high linear energy transfer particles (10B + 1nth----[11B]----4He(alpha) + 7Li + 2.79 MeV). The F98 tumor is an anaplastic glioma of CD Fischer rat origin with an aggressive biological behavior similar to that of human glioblastoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…For the high dose of BSH, the half-times were in reasonably good agreement with the results of Clendenon, et al, 5 also eliminated from the blood in two phases; the slow second elimination phase suggested that there is a depot compartment from which there is slow release back into the blood. The transfer coefficients resulting from the compartment analysis reflected this behavior, and the pattern of uptake in the tumor for BOPP, with a maximum tumor concentration time of 24 hours, further supported this interpretation.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…For the high dose of BSH, the half-times were in reasonably good agreement with the results of Clendenon, et al, 5 also eliminated from the blood in two phases; the slow second elimination phase suggested that there is a depot compartment from which there is slow release back into the blood. The transfer coefficients resulting from the compartment analysis reflected this behavior, and the pattern of uptake in the tumor for BOPP, with a maximum tumor concentration time of 24 hours, further supported this interpretation.…”
Section: Discussionsupporting
confidence: 86%
“…Abe, et al, 2 presented tumor-to-blood ratios mostly below or around unity, in agreement with both the results of Joel, et al, 14 and with this study. The tumor-to-blood ratios reported by Clendenon, et al, 5 were somewhat higher, with a peak value of 5 at 6 hours after the injection.…”
Section: Discussionmentioning
confidence: 71%
“…The morphology of the F98 EGFR glioma was indistinguishable on H&E-stained sections from that of the F98 WT glioma, as was previously described by us [33]. The tumor was composed of a mixed population of spindle shaped cells with fusiform nuclei, frequently forming a whorled pattern of growth, and a smaller subpopulation of polygonal cells with round to oval nuclei.…”
Section: Resultssupporting
confidence: 58%
“…Untreated control rats had large (TSI = 3.4) highly invasive tumors that had the characteristic appearance of the F98 glioma (Clendenon et al, 1990). Animals that received 127 I-IUdR alone, administered by Alzet osmotic pumps, generally had smaller tumors (TSI = 2.33), and one out of eight rats was tumor free.…”
Section: Neuropathologic Evaluationmentioning
confidence: 99%